Paciente de 89 años de edad sexo femenino con neumonía grave de la comunidad más insuficiencia respiratoria restrictiva - Casilla Ruiz, Neyva Fernanda (2020)
Geriatric patients are considered a sensitive group to acquire various pathologies due to the variety of risk factors that endanger their health, such as cardiovascular diseases, respiratory diseases, immune disorders related to aging, etc. Pneumonia is an acute inflammatory process of the lung parenchyma of infectious origin that in older adults is usually responsible for a high mortality rate. Among the most common bacteria that cause pneumonia are Streptococcus pneumoniae and Haemophilus influenzae. Respiratory Failure is a pathology in which there will be a decrease in blood oxygen values or cause the increase of carbon dioxide in the blood in a dangerous way for health, this pathology usually goes hand in hand with another disease and both must be corrected for the patient to progress positively. The objective of this clinical case is to know better about these diseases and the risk that an older adult suffers from, so that they can act quickly and quickly until they reach an effective treatment.